APPLICATION PECULIARITIES OF TOOLS FOR ENSURING A BALANCED USE OF AGRICULTURAL LAND - Yasinetskа І.А.; Кushnirukк Т.М.; Dodurych , V.V. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The article describes the main economic issues of the financial and economic mechanism as a comprehensive system of instruments in the market conditions and systematizes the main directions of this task, which ultimately aims to promote the reproduction and preservation of agricultural potential of regions and intensify rural development of Ukraine. Theoretical and methodological approaches to the expansion and stabilization of material and resource provision of balanced use of agricultural land have been formed. The key requirement for the formation success and effective functioning of the financial and economic mechanism and its components, tools and levers for resource provision of balanced agricultural land use is compliance with legal, organizational, economic principles and conceptual approaches, systematized in the paper. The need for development and implementation of the system of financial and economic instruments in economic activity is substantiated on this basis. It is proved that the effectiveness of the introduction of the system of financial and economic instruments, as components of the appropriate mechanism to ensure balanced land use in the field of agricultural production requires the introduction of market circulation of agricultural land. Recently, the potential of financial and economic preconditions for ensuring a balanced level of agricultural land use in Ukraine is not used at a sufficient level. The direction of attracting financial and economic instruments remains not fully involved and on this basis the agricultural sector is short of investment, which requires state regulation. Investments are the most important means of ensuring progressive structural changes in environmental protection, ensuring an acceptable level of agri-environmental safety and balanced use of agricultural land.